2017
DOI: 10.1002/prca.201700082
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signature of Microvesicles from Umbilical Cord Mesenchymal Stem Cells of Preterm and Term Infants

Abstract: MVs from MSCs conduct aerobic metabolism similarly to exosomes from the same cells, with interesting differences related to their biogenesis and function. The clinical relevance of the study lays in the perspective to utilize MVs as promising sensor of the inflammatory and metabolic state of the preterm newborn, to help in preventing the complications of prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…Otherwise, for example, the mitochondrial superoxide dismutase would have been highlighted. This is consistent with the hypothesis that the oxidative damage may derive from an OxPhos dysfunction both inside the mitochondria and in ectopic locations, that has been reported in plasma membranes, 41‐45 myelin sheath, rod disks, exosomes, and MV 17,46‐48 . The expression of mitochondrial components of the electron transfer chain (ETC) and F o F 1 ‐ATP synthase in ectopic sites not protected by a double membrane poses greater risks for oxidative stress generation and implies the involvement of GSS.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Otherwise, for example, the mitochondrial superoxide dismutase would have been highlighted. This is consistent with the hypothesis that the oxidative damage may derive from an OxPhos dysfunction both inside the mitochondria and in ectopic locations, that has been reported in plasma membranes, 41‐45 myelin sheath, rod disks, exosomes, and MV 17,46‐48 . The expression of mitochondrial components of the electron transfer chain (ETC) and F o F 1 ‐ATP synthase in ectopic sites not protected by a double membrane poses greater risks for oxidative stress generation and implies the involvement of GSS.…”
Section: Discussionsupporting
confidence: 90%
“…Inflammation, hyperoxia, and ischemia challenge the newborn, and free radical‐induced oxidative stress production is almost a paradigm of prematurity 15,16 . In fact, antioxidant defense mechanisms are incompletely developed in preterm newborns 16‐18 . Our ELISA test on newborn serum showed that the elevated levels of reactive oxygen species (ROS) in the preterm were reduced in the treated preterm cohort.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Importantly, FZD2 is the receptor of Wnt5a/b and FZD2 mutations in uence Wnt signaling, which mediates the epithelial to mesenchymal transition (EMT) during lung development [50]. In addition, by comparing the proteome of microvesicles collected from hUC-MSC CM between preterm and term groups, Bruschi et al found that 173 proteins were signi cantly changed, 163 of which were increased in the preterm group [51]. However, there have been no comprehensive comparisons of hUC-MSC CM peptidomic pro les between preterm and term infants.…”
Section: Discussionmentioning
confidence: 99%